Нечіткий метод групового урахування аргументів за невизначеними вхідними даними - Zaychenko, Yu. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The Fuzzy GMDH is extended for the case of fuzzy input data given in the form of uncertainty intervals. The mathematical model of this problem was constructed and the corresponding algorithm suggested: so called FGMDH with fuzzy inputs. The experimental investigations of the suggested algorithm were carried put and their results are presented for the problem of stock exchange forecasting.